Assessing the Economic and Social Impact of Tax and Transfer System Reforms: A General Equilibrium Microsimulation Approach - Peter Benczur; Gabor Katay; Aron Kiss (Publications Office of the European Union, 2017)
We present a general-equilibrium behavioural microsimulation model designed to assess long-run macroeconomic, fiscal and social consequences of reforms to the tax and transfer system. The behaviour of labour supply is assessed along both the extensive and intensive margins, by merging the discrete choice and the elasticity of taxable income approaches. General-equilibrium feedback effects are simulated by embedding microsimulation in a parsimonious macro model of a small open economy. We estimate and calibrate the model to Hungary, and then perform three sets of simulations. The first one explores the impact of personal income tax reductions that are identical in cost but different in structure. The second one compares three different tax shift scenarios, while the third one evaluates actual policy measures between 2008 and 2013. The results suggest that while a cut in the marginal tax rate of high-income individuals may boost output, it does not have a significant employment effect. On the other hand, programs like the Employee Tax Credit do have a significant employment effect. We find that the policy measures introduced since 2008 substantially increase income inequality in the long run; the contribution of the changes after 2010 are about four times that of the changes before 2010. Our results highlight that taking account of household heterogeneity is crucial in the analysis of the macroeconomic effects of tax and transfer reforms.
Keywords: H22; H31; C63; 330; behavioural microsimulation; linked micro macro model; tax system; transfers